Polysilazane-derived electrospun SiCN fiber mats: characterization and application in electromagnetic field shielding and electrochemical energy storage - Ramlow, Heloisa (2022)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Engenharia Química, Florianópolis, 2022.